2023
DOI: 10.3389/fpls.2022.1056082
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial volatile organic compounds (VOCs) promote growth and induce metabolic changes in rice

Abstract: Plant growth-promoting bacteria (PGPB) represent an eco-friendly alternative to reduce the use of chemical products while increasing the productivity of economically important crops. The emission of small gaseous signaling molecules from PGPB named volatile organic compounds (VOCs) has emerged as a promising biotechnological tool to promote biomass accumulation in model plants (especially Arabidopsis thaliana) and a few crops, such as tomato, lettuce, and cucumber. Rice (Oryza sativa) is the most essential foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 104 publications
1
13
0
Order By: Relevance
“…As aforementioned, Bacillus spp. could often produce bVOCs that may act as external signals among intra-, inter-species, and even inter-kingdoms (14,32). To examine if the increased tolerance response by the BzaHS1 strain was due to bVOCs released from the strain, we designed a stacked magenta box system to spatially isolate roots from the BzaHS1 strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As aforementioned, Bacillus spp. could often produce bVOCs that may act as external signals among intra-, inter-species, and even inter-kingdoms (14,32). To examine if the increased tolerance response by the BzaHS1 strain was due to bVOCs released from the strain, we designed a stacked magenta box system to spatially isolate roots from the BzaHS1 strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies illustrate the role of PGPR, including Bacillus spp., Pseudomonas spp., and Rhizobium spp., in regulating abiotic stress tolerance, as well as induced resistance, through direct and indirect mechanisms (11,12,14,15,16,41). Our previous study proposed that exogenous treatment of the BzaHS1 strain might activate IST to protect plants from high salinity stress (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryu et al (2003) [ 41 ], first reported the positive impact caused by bacterial volatiles promoting the growth of Arabidopsis, since then very few research was conducted on the growth promotion of rice by the action of bacterial volatiles [ 10 ]. In our experimental setup, six isolates were used to see if their volatiles could promote rice growth when grown on two petri plates with only airborne signals being transferred between the bacteria and the plants.…”
Section: Discussionmentioning
confidence: 99%
“…From literature approximately 2000 VOCs have been identified which were emitted by a bacteria and fungi and were discovered on a limited number of microorganisms. BVCs are categorized in alcohols, alkenes, ketones, tepenoids, and other chemical classes [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%